Role of Institutions: A Case of Plastic Industry Entrepreneur - Kar, Brajaballav; Kar, Satyaballav (AMC Indian Journal of Entrepreneurship, 2022)
Entrepreneurial effort depends on self-efficacy. Own skillset is a part of self-efficacy. The present case study brings out the role of ambition, self-efficacy, and attitude towards entrepreneurship in venture formation. The persistency is evidenced when an entrepreneur tried, failed, learnt from mistakes, went back to industry to learn, and attempted again. Beyond the traditional aspects of entrepreneurship, this narrative research points to the role of educational institutes in promoting nascent technology entrepreneurship, the role of financial institutions, and natural calamity among others. The entrepreneur in this case asserted that the early childhood stories of his father’s admiration of entrepreneurs, and the news of entrepreneurial achievements were motivating factors for career choice. Initial failure, subsequent re-learning, institutional support, and continual education are pivots of this research. However, the entrepreneur’s reflection brought out how customers and suppliers try to take advantage of a new firm due to information asymmetry and bargaining power. Though the information asymmetry issue in institutional finance to entrepreneurship is well documented, an adversarial initial relationship among new firm, customers, and suppliers are less researched upon andis an opportunity for future research. Firm survival depends on responding to such challenges of market entry, network-dynamics, and information asymmetry.